Movements and Parties: Beyond Contentious Performances - Abers, Rebecca Neaera; Rezende de Almeida, Débora Cristina; von Bülow, Marisa (PARTECIPAZIONE E CONFLITTO, 2023)
For Symposium Absstract is not required